ANALISIS PENGARUH KOMPOSISI DAN UKURAN NANOKOMPOSIT LiFePO4 - Siddiq, Nur Abdillah; Fauzan A., Ahmad; Abdillah, Firqi; Alifah, Miratul; Fadhilah, Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Lithium ion batteries was currently used as an energy source for portable electronic devices and more promising than others. But the conventional LiFePO4 has low ionic diffusivity. Flame spray pyrolysis method was developed as a particle synthesis method. This research reports the effect of LiFePO4 particle size and composition in lithium batteryperformance. As free variables of this research are the carrier gas flow rate and concentration of glucose. From the results obtained, the higher the flow rate of carrier gas so that decrease diffusivity and the higher the glucose concentration so that increase diffusivity.Keywords: LiFePO4, flame spray pyrolysis, diffusivity, particle size, glucose concentration.